FORMULATION AND IN VITRO PENETRATION TESTING OF NUTMEG SEED OIL (Myristica fragrans Houtt.) NANOEMULGEL - Lailah, Nashfiatun Nur; Syaputri, Fauziah Ningrum; Larasati, Rizky Dwi; Fatimi, Hana Anisa; Manurung, Devi Yanthre Sari (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Nutmeg seed oil has a low absorption time and is unstable during storage; therefore, so to facilitate this it is made in a nanoemulgel form because it can increase contact time and increase drug penetration into the skin. This study aimed to determine the effect of variations in nutmeg seed oil concentration on the physical characteristics and penetration rate of nanoemulgel preparations. Nanoemulgel was made by mixing the nanoemulsion phase into a gel base with oil concentrations of 4.5%, 5%, and 5.5%. The nanoemulsion physical characteristics results are 90.7–91.1% for the turbidimetry test, 453–516 nm for particle size, 42.4–48.6 mV for the zeta potential test, 6.46–6.66 for the pH test, and O/W for nanoemulsion type. Physical characteristics included organoleptic tests, homogeneity, pH, adhesive power, spreadability, viscosity, and rheology. The penetration rate was determined using the Franz diffusion-cell method. The results showed that the nanoemulgel preparation was white in color and had a characteristic smell of nutmeg oil, a semisolid, homogeneous texture, skin pH of 4.5–6.5, spreadability met the range of 5–7 cm, adhesion of >4 seconds, viscosity of 4000–50000 cPs, and pseudoplastic flow properties. The best formulas are found in Formulas 1 and 2 because the stability test meets the requirements for good physical characteristics. Variations in the concentration of nutmeg oil did not show any influence on the penetration rate, with the flux values ??obtained for each formula being F1 0.0117 mg/cm2hour-1, F2 0.0126 mg/cm2hour-11, and F3 0.0246 mg/cm2hour-1.